2014
DOI: 10.1177/2324709614545225
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Peripheral Neuropathy

Abstract: The health risks and side effects of fluoroquinolone use include the risk of tendon rupture and myasthenia gravis exacerbation, and on August 15, 2013, the Food and Drug Administration updated its warning to include the risk of permanent peripheral neuropathy. We present a case of fluoroquinolone-induced peripheral neuropathy in a patient treated for clinically diagnosed urinary tract infection with ciprofloxacin antibiotic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
0
21
0
4
Order By: Relevance
“…According to a study by Etminan et al, FQs showed a higher risk of causing peripheral neuropathy (relative risk (RR) = 1.83, 95% CI 1.49–2.27) [33]. A case report published by Francis et al presented a case with CFX-induced peripheral neuropathy [11]. The increased reports of neurological-related ADRs to FQs compared to other antibiotics may be due to a periodic warning by the FDA and recent changes in the labeling of the FQ class.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a study by Etminan et al, FQs showed a higher risk of causing peripheral neuropathy (relative risk (RR) = 1.83, 95% CI 1.49–2.27) [33]. A case report published by Francis et al presented a case with CFX-induced peripheral neuropathy [11]. The increased reports of neurological-related ADRs to FQs compared to other antibiotics may be due to a periodic warning by the FDA and recent changes in the labeling of the FQ class.…”
Section: Discussionmentioning
confidence: 99%
“…It is perceived to be caused mainly due to systemic FQs. The symptoms of peripheral neuropathy are usually quick and appear within a couple of days after use, but its identification may be delayed due to its vague clinical manifestation [11]. In some instances, the adverse effects progressed for over a year, regardless of stopping the medication [12].…”
Section: Introductionmentioning
confidence: 99%
“…В то же время НР со стороны желудочно-кишечного тракта среди сообщений в отечественной базе данных занимают только третью позицию. Вероятной причиной такого изменения структуры может быть иной профиль безопасности фторированных производных хинолона, характеризующийся более низкой вероятностью развития желудочнокишечных расстройств, чем у хинолонов первого поколения [13].…”
Section: Discussionunclassified
“…В литературе имеются свидетельства появления долгосрочных неблагоприятных эффектов со стороны периферической нервной системы (ПНС) при использовании фторхинолонов [13]. Предполагаемая частота нейропатии у пациентов, получавших ципрофлоксацин, составляет один случай на 17 000 пациентов [25], то есть такая НР возникает очень редко.…”
Section: Discussionunclassified
“…Chora została poddana szeregom testów i badań, by wyjaśnić przyczynę zgłaszanych dolegliwości -otrzymane wyniki nie ujawniły schorzenia, które mogłoby charakteryzować się wspomnianymi objawami. Dolegliwości bólowe są na tyle przykre i utrudniają codzienne funkcjonowanie do tego stopnia, że pacjentka musi stosować amitryptylinę w dawce 20 mg raz na dobę [16].…”
Section: Fluorochinolony a Neuropatiaunclassified